2022
DOI: 10.1111/jch.14582
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of wide pulse pressure in an elderly Chinese population: A cross‐sectional study

Abstract: Blood pressure and pulse pressure (PP) had their own characteristics in the elderly population. This cross‐sectional study including 5030 elderly participants was conducted to describe the distribution of blood pressure and wide PP in the elderly population and find influencing factors of wide PP. Wide PP was defined as PP equal to or more than 65 mmHg, and was classified three types as low systolic blood pressure (SBP) and low diastolic blood pressure (DBP) (LSLD), high SBP and low DBP (HSLD), and high SBP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…The average of the two measured PP was used for the analysis. As in most previous studies, wide PP was defined as PP above 65 mmHg [ 7 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average of the two measured PP was used for the analysis. As in most previous studies, wide PP was defined as PP above 65 mmHg [ 7 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In China, several regional surveys with limited sample sizes and different age coverages reported different prevalence rates of wide PP. For instance, a study among Han Chinese aged 18–74 years in Hebei, Zhejiang, and Guangxi Provinces reported a prevalence of 6.7% [ 6 ], whereas the Yiwu Elderly Cohort Study among 5030 adults older than 65 years living in Jiangsu Province reported 54.2% participants as wide PP [ 7 ]. However, there is insufficient information from large-scale nationwide studies on the age-specific and sex-specific distributions of PP among the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension (HT) was de ned as SBP ≥ 140 mmHg or DBP ≥ 90 mmHg or the use of antihypertensive medications [16]. Clinically signi cant WPP was identi ed as PP ≥ 65 mmHg [5]. Current smokers or individuals with a history of tobacco use were classi ed as smokers.…”
Section: De Nitionsmentioning
confidence: 99%
“…The difference between systolic blood pressure (SBP) and diastolic blood pressure (DBP), known as pulse pressure (PP), represents the maximal and minimum pressure alterations during blood circulation [4]. The normal PP value is approximately 40 mmHg, while PP 65 mmHg is considered as wide PP (WPP) [5]. WPP has been shown to be associated with chronic disease such as diabetes mellitus (DM), stroke and chronic kidney disease (CKD) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lain menunjukkan bahwa lansia dengan tekanan sistolik 130 mmHg atau lebih tinggi memiliki kinerja fisik yang lebih baik dibandingkan dengan mereka yang memiliki TD lebih rendah. Temuan ini menunjukkan bahwa penurunan TD yang berlebihan dapat merusak pada lansia dengan fungsi fisik atau kognitif yang memburuk (Yang et al, 2022). TD yang rendah dapat menyebabkan perfusi yang tidak memadai dari organ-organ sentral, yang paling penting adalah jantung, yang melakukan perfusi selama diastolik.…”
Section: Kemunduran Biologisunclassified